Higher Bioavailability of Calcium in Chickens With a Novel In-Feed Pharmaceutical Formulation - Carrillo, Lizbeth; Bernad, María-José; Monroy-Barreto, Minerva; Coello, Carlos L.; Sumano, Héctor; Gutiérrez, Lilia (Frontiers in Veterinary Science, 2020)
Egg production and egg shell quality decrease towards the end of the first laying cycle in hens (approximately by week 80). Even so, farmers often choose to work a second cycle with them. Defective egg shell production has been mainly linked to a decrease in gastrointestinal absorption of calcium. Here we studied pharmaceutically-designed modified-release small pellets (FOLAs) containing calcium to improve calcium bioavailability (F). The influence of FOLA alone or with capsicum-oleoresin was studied in a total of 400 Bovans-White hens randomly divided into four groups of 20 laying hens each and with 5 replicates per group (n=100) as follows: 1) control group (GC) receiving a diet containing basal levels of 4.1% of calcium-carbonate; 2) group GF treated as GC but with the same dose of calcium-carbonate in FOLA; 3) group GFc5 was treated as GF but with 6 ppm of capsicum-oleoresin (500,000 Scoville Heat Units [SHU]); and 4) group GFc10 treated as GFc5 but with 1,000,000 SHU capsicum-oleoresin. Plasma concentrations of calcium were determined during 5 days at predetermined times sampling more often on days 1 and 5 for blood plasma kinetics of calcium. Relative bioavailability (Fr) values based on the area under the serum calcium concentration vs. time curve (AUC) were obtained and compared to GC. The AUC was statistically different among all groups (P < 0.5), but the GFc10 had the greatest Fr (194%), with serum calcium concentrations ranging from 25.37 to 31.2 µg/dL. Calcium residence time (RT) between GC and GF showed no statistical differences while GFc5 and GFc10 had statistically superior RT values. Simultaneously, the number of shell-less eggs per group and their thickness was evaluated by utilizing the same groups but with 150 hens per group on 6 d. Shell-less eggs decreased to zero in Group GFc10 and produced eggs with the greatest shell thickness from day two onwards. The inclusion of calcium-carbonate in the pharmaceutical form FOLA induced higher serum calcium concentrations (GF, GFc5, and GFc10) particularly during the night-phase of the hen’s cycle—this coincides with the time at which egg shell formation occurs.